Effects of tomato peel as fat replacement on the texture, moisture migration, and sensory quality of sausages with varied fat levels. Issue 4 (2nd October 2017) - Wang, Qiang; Wu, Hongbin; Xie, Yuejie; Chang, Haijun; Li, Xue; Liu, Chengjiang; Xiong, Zhengwei
ABSTRACT: The influence of tomato peel powder on the water holding capacity, microstructural character, and sensory quality of reduced-fat sausages during storage was investigated. In this work, rough tomato peels were crushed to powders of 0.15- and 0.025-mm particle sizes by conventional crushing and airflow ultramicro-crushing, respectively. Replacing fat with tomato powder significantly increased the amount of free water in sausages after storage, as determined by low-field nuclear magnetic resonance imaging. However, less free water was present in sausage samples that were already of the reduced-fat variety. Sausages with the conventional mechanically crushed tomato powder showed denser and more compact structures than sausages with those using the airflow ultramicro-crushed powder. Compared to the case of sausages with higher levels (3%) of tomato peel, granulation was more obvious ( p < 0.05) in samples with lower levels of tomato peel (0.5%), and more pores were observed in the samples with higher tomato powder content. The results indicated that low doses of conventionally crushed tomato powder as a potential fat substitute could be used in the sausage industry.